Saving Quinton - Sorensen, Jessica (New York : Forever, 2015)
From the # 1 New York Times bestselling author of Breaking Nova comes a gripping story about what it takes to save the one you love. Nova Reed can't forget him-Quinton Carter, the boy with the honey-brown eyes who made her realize she deserved more than an empty life. His pain was so similar to her own. But Nova has been coming to terms with her past and healing, while Quinton is out there somewhere, sinking deeper. She's determined to find him and help him. before it's too late. Nova has haunted his dreams for nearly a year-but Quinton never thought a sweet, kind person like her would care enough about a person like him. To Quinton, a dark, dangerous life is exactly what he deserves. And Nova has no place in it. But Nova has followed him to Las Vegas, and now he must do whatever it takes to keep her away, to maintain his self-imposed punishment for the unforgivable things he's done. But there's one flaw in his plan: Nova isn't going anywhere.
Keywords: Man-woman relationships -- Fiction; Love stories